Efektifitas Back Massage Menggunakan Minyak Esensial Clary Sage terhadap Produksi ASI Pada Ibu Nifas Pasca Bedah Sesarea - Rosyidah, Rafhani; Azizah, Nurul (Journal of Issues in Midwifery, 2018)
Pain, anxiety disorder, and limited mobilization in post-caesarean mothers cause delayed lactogenesis processes. Back massage with clary sage essential oil is one of the obstetric actions that can help postpartum mother in increasing milk production, so can give exclusive breastfeeding for newborn baby. The purpose of this study was to analyze the effectiveness of back massage using clary sage essential oil to the ASI post-cesarean prophylaxis. The research design used quasi experiment with post test only non equivalent control group design, sampling technique by consecutive sampling with the number of samples counted 60 respondents divided into 3 groups. Data analysis using MANOVA test with significance value P <0,05. The results obtained P value of 0,000 which means there is the effect of back massage using clary sage essential oil on milk production after cesarean section.